Nauczyciel wczesnej edukacji z krótkim stażem w zawodzie – praca w stanie wyjątkowym - Małgorzata Żytko (Problemy Wczesnej Edukacji)
This article addresses the issue of prestige and social recognition in the teaching profession with up to years of short seniority. The challenge that teachers face on a daily basis is to function in a context of high social expectations and demands, while at the same time, the social prestige of the profession is declining and its value is being depreciated. Appreciation of the profession is closely linked to perceiving and respecting the importance of education in personal, social, and political terms. This issue became the subject of a study carried out in 2021 among a group of more than 800 primary and pre-school teachers in Warsaw, with work experience of not more than 5 years. The aim of the survey was to describe the factors that give satisfaction, motivate, or demotivate teachers to work, with a particular focus on the sense of recognition and social prestige. The results indicate that half the teachers surveyed were considering leaving school and changing professions.